Synthesis of highly functionalized C60 fullerene derivatives and their applications in material and life sciences. Issue 1 (20th October 2014) - Yan, Weibo; Seifermann, Stefan M.; Pierrat, Philippe; Bräse, Stefan
Abstract : Highly functionalized fullerenes can be efficiently constructed by various techniques. Abstract : Highly functionalized fullerenes can be efficiently constructed by various techniques. However, the challenge is to synthesize highly symmetrical fullerenes. Recently, a number of X-ray structures have been disclosed showing the high symmetry of substituted fullerenes. By reviewing the major types of multi functionalized fullerenes through selected examples with a link to the structural assignments, the authors intend to give a concise overview to the specialist in the field and to provide the non-specialist with a tool box of possibilities.